Evaluation and Further Development of the B2B Startup Experimentation Framework: Application in B2C E-Commerce - Carsten H. Hahn; Vili Sotirova; Patrick Brecht; Anja Ströbele (Athens Journal of Business & Economics)
Different challenges and uncertainty arise from digital transformation as managers are forced to find new channels or make alternative investments decisions. Companies can use experiments as knowledge-generating resources to mitigate the uncertainty surrounding the adapted business model. The B2B Startup Experimentation Framework (B-SEF) was developed for startups in the B2B environment to discover and validate a business model’s desirability through business experiments. This study uses the criteria completeness, consistency, plausibility, accuracy, and feasibility to investigate to what extent the B-SEF can be adapted to conduct business experiments in a B2C environment. Based on the B-SEF approach, two experimentation rounds are conducted regarding multiple online advertising channels and their efficiency in generating new customers in a B2C cosmetic online shop. Findings show that the B-SEF’s generic structure is also suitable for conducting business experiments in the B2C environment when two adjustments are made regarding the sales funnel in the macro-level of the framework. First, the funnel levels required reordering to represent the customer journey better. Second, the new funnel level “awareness” needs to be added, as tracking awareness is relevant in the success of an e-commerce store. This research contributes by providing a guideline for entrepreneurs who want to conduct similar business experiments and extracting the company’s most and least efficient advertising channels to acquire new profitable customers. The study’s originality lies in assessing the B-SEF’s suitability in the B2C context and providing a tool for its application to conduct business experiments comprehensively and successfully, especially regarding documentation and data collection.